Kontroversi Dakwah Gus Miftah dalam Diskursus Digital: Analisis Sosio-Kultural Respon Nitizen - Fikri, Mursyid (Jurnal Komunikasi Islam, 2025)
The controversy surrounding Islamic preaching (da’wah) involving a prominent religious figure in Indonesia, Miftah Maulana Habiburrahman, well known as Gus Miftah, arose from his use of the word "Goblok" toward an iced tea seller during a religious gathering (pengajian), which became a topic of public discourse on social media at the end of 2024. The statement triggered a polarized response on platforms such as Instagram, TikTok, Twitter, and Meta, reflecting the dynamics of social and religious values in digital media discourse. This study aims to analyze netizens’ responses to the controversy surrounding Gus Miftah’s statement as a form of preaching discourse on social media. Using discourse analysis, the study’s results showed a polarization of netizen responses into two groups: critical expressions and support. Those who expressed criticism highlighted violations of moral and social norms, while those who supported Gus Miftah’s statement emphasized the need to contextualize it properly to avoid misunderstanding.